Clinicopathological study of cervical lymphadenopathy at rural tertiary health care centre - M. Paikrao, Yogesh; M. Deshpande, Prashant; N. Chintale, Kailas (International Journal of Advances in Medicine, 2018)
Background: The term lymphadenopathy refers to nodes that are abnormal in size, consistency or number. Cervical lymphadenothy is one of the common and important presentations of the underlying pathology of the head and neck region which has large number of differential diagnosis like neoplasms, infections (specific and non-specific) and in immune deficiency disorders and also, the rare disorders like Inflammatory pseudotumour (Plasma cell granuloma) and Kikuchi-Fujimoto diseases. Etiological profile of cervical Lymphadenopathy varies from region to region, in developing countries like India, acute respiratory infection, suppurative skin infection and tuberculosis are the main causes for cervical lymphadenopathy while in developed countries secondary carcinoma are the most frequent causes for cervical lymphadenopathy. Methods: This hospital based cross sectional study was carried out in the Department of Otorhinolaryngology in Rural Tertiary Health Care Centre. The period of the study was from January 2014 to June 2016. Results: In our study of 176 patients the youngest patient was 13year of age and oldest patient was 68 years old. The majority of patients affected were in the age group of 21 to 30 years (30.68%) followed by 13 to 20 years (23.86%). The least affected age group was 60 to 70 years (5.8%). There were 80 men and 96 women. The male to female ratio in present study was 1:1.2 The frequently affected age group was 21 to 30 years in men (26.25%) as well as women (34.38%). In our study Neck swelling was present in all cases (100%). fever was the second most common symptom in 54 cases (30.68%) followed by cough in 45 cases (25.56%). In our study most frequently involved lymph node group was posterior cervical in 68 cases (38.39%), followed by upper deep cervical in 66 cases (37.50%). Conclusions: In the present study it was found that tuberculosis was the most frequent cause of cervical Lymphadenopathy in 48.29% of patients, followed by reactive Lymphadenopathy in 17.34%, metastatic lymphadenopathy in 15.34% chronic nonspecific Lymphadenopathy in 14.77% and primary lymphoreticular malignancy in 4.35%. In our study out of 176 cases of cervical lymphadenopathy 141 cases (80.11%) were non neoplastic and 35 cases (19.88 %) were neoplastic.